MRI Findings of Disc Degeneration are More Prevalent in Adults with Low Back Pain than in Asymptomatic Controls: A Systematic Review and Meta-Analysis - Brinjikji, W. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Imaging features of spine degeneration are common in symptomatic and asymptomatic individuals. We compared the prevalence of MR imaging features of lumbar spine degeneration in adults 50 years of age and younger with and without self-reported low back pain. MATERIALS AND METHODS: We performed a meta-analysis of studies reporting the prevalence of degenerative lumbar spine MR imaging findings in asymptomatic and symptomatic adults 50 years of age or younger. Symptomatic individuals had axial low back pain with or without radicular symptoms. Two reviewers evaluated each article for the following outcomes: disc bulge, disc degeneration, disc extrusion, disc protrusion, annular fissures, Modic 1 changes, any Modic changes, central canal stenosis, spondylolisthesis, and spondylolysis. The meta-analysis was performed by using a random-effects model. RESULTS: An initial search yielded 280 unique studies. Fourteen (5.0%) met the inclusion criteria (3097 individuals; 1193, 38.6%, asymptomatic; 1904, 61.4%, symptomatic). Imaging findings with a higher prevalence in symptomatic individuals 50 years of age or younger included disc bulge (OR, 7.54; 95% CI, 1.28–44.56; P = .03), spondylolysis (OR, 5.06; 95% CI, 1.65–15.53; P < .01), disc extrusion (OR, 4.38; 95% CI, 1.98–9.68; P < .01), Modic 1 changes (OR, 4.01; 95% CI, 1.10–14.55; P = .04), disc protrusion (OR, 2.65; 95% CI, 1.52–4.62; P < .01), and disc degeneration (OR, 2.24; 95% CI, 1.21–4.15, P = .01). Imaging findings not associated with low back pain included any Modic change (OR, 1.62; 95% CI, 0.48–5.41, P = .43), central canal stenosis (OR, 20.58; 95% CI, 0.05–798.77; P = .32), high-intensity zone (OR = 2.10; 95% CI, 0.73–6.02; P = .17), annular fissures (OR = 1.79; 95% CI, 0.97–3.31; P = .06), and spondylolisthesis (OR = 1.59; 95% CI, 0.78–3.24; P = .20). CONCLUSIONS: Meta-analysis demonstrates that MR imaging evidence of disc bulge, degeneration, extrusion, protrusion, Modic 1 changes, and spondylolysis are more prevalent in adults 50 years of age or younger with back pain compared with asymptomatic individuals.